Quality of Life in Diabetic Foot Ulcer: Associated Factors and the Impact of Anxiety/Depression and Adherence to Self-Care. (June 2020) - Polikandrioti, Maria; Vasilopoulos, Georgios; Koutelekos, Ioannis; Panoutsopoulos, Georgios; Gerogianni, Georgia; Babatsikou, Fotoula; Zartaloudi, Afroditi; Toulia, Georgia
Diabetic foot ulcer (DFU) is a major complication of diabetes mellitus that needs a multidisciplinary approach. The purpose of this study was to assess the impact of patients' characteristics, anxiety/depression, and adherence to guidelines on the QoL of patients with diabetic ulcer. The sample of the study consisted of 195 patients. Data collected by the completion of SF-36 Health Survey, the Hospital Anxiety and Depression Scale, and a questionnaire that measured adherence to self-care activities. Patients had moderate- to high-quality levels in emotional well-being, pain, social functioning, and energy/fatigue (median: 68, 68, 63, and 60, respectively), while they had low levels of quality in physical functioning, role physical, and role emotional (median: 21, 0, and 33, respectively). In their general health, patients had moderate levels (median: 50). High levels of anxiety and depression were observed in 13.8% and 20.0% of the participants, respectively. After multiple regression, regarding general QoL, patients living in the capital city had 9.89 points worse general health than patients living in Attica (β = −9.89, 95% confidence interval [CI] = −16.86 to 2.93, P = .006). Patients with moderate or high levels of anxiety had 9.37 and 16.08 points, respectively, worse general health than those with low levels (β = −9.37, 95% CI = −17.04 to 1.70, P = .017, and β = −16.08, 95% CI = −26.65 to −5.51, P = .003, respectively). Clinically, these findings may help health professionals attain effective treatment of emotional burden to DFU patients and increase adherence to self-care.